2021
DOI: 10.31014/aior.1993.04.02.243
|View full text |Cite
|
Sign up to set email alerts
|

L2 Motivational Self System and Learning Approaches of High School Students

Abstract: The Education Quarterly Reviews is an Open Access publication. It may be read, copied, and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.The Asian Institute of Research Education Quarterly Reviews is a peer-reviewed International Journal. The journal covers scholarly articles in the fields of education, linguistics, literature, educational theory, research, and methodologies, curriculum, elementary and secondary education, higher education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
0
0
1
Order By: Relevance
“…The questionnaire result showed that the tenth-grade students in SMK Negeri 1 Singaraja in the Hotel Accommodation program tend to perform in the surface approach. This finding is similar to Irgatoğlu (2021) who found that the surface approach was the dominant approach used by students in Turkey towards learning foreign languages. Similar findings on high school students in the Indonesian context, according to Mulyani et al (2020) on their study suggest that the tendency of students in learning English was at surface level.…”
Section: Discussionsupporting
confidence: 89%
“…The questionnaire result showed that the tenth-grade students in SMK Negeri 1 Singaraja in the Hotel Accommodation program tend to perform in the surface approach. This finding is similar to Irgatoğlu (2021) who found that the surface approach was the dominant approach used by students in Turkey towards learning foreign languages. Similar findings on high school students in the Indonesian context, according to Mulyani et al (2020) on their study suggest that the tendency of students in learning English was at surface level.…”
Section: Discussionsupporting
confidence: 89%
“…Las conclusiones del estudio de Andreou et al ( 2004) fueron consistentes con los trabajos anteriormente mencionados, ya que los investigadores encontraron diferencias de género en relación con la estrategia y el logro. Con respecto a la estrategia, los hombres percibieron que adoptaban un enfoque más profundo que las mujeres y dijeron tener niveles más altos de autoconfianza académica, mientras que las mujeres tenían un enfoque más superficial que los hombres Los estudios también aseveran que las mujeres parecen hacer uso con más frecuencia de las estrategias en su proceso de aprendizaje de una L2 (Liyanage y Bartlett, 2012;Irgatoğlu, 2021). De manera más específica, Ehrman y Oxford (1989) y Magogwe y Oliver (2007) concluyen que las mujeres de su estudio de caso emplean de manera más asidua con respecto a los hombres, las estrategias metacognitivas.…”
Section: Factores Personales Y Académicosunclassified